Pancasila, Piagam Madinah, dan Konstruksi Fikih Kebangsaan Ala Pesantren: Studi Hasil Bahth al-Masa>il Forum Musyawarah Pondok Pesantren (FMPP) XXX Tahun 2016 - Syaiful Bahri; Syamsul Anwar; Mochamad Sodik (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This paper analyses one of the decisions reached by the baá¸¥th al-masÄil Islamic Boarding School Deliberation Forum (FMPP) in Java and Madura in 2016 at the Babakan Islamic Boarding School in Ciwaringin, Cirebon. In its decision, baá¸¥th al-masÄil FMPP stated that Pancasila as the State's foundation is consistent with the values enshrined in the Medina Charter. The issues that will be addressed in this study are: first, how does baá¸¥th al-masÄil FMPP use the argumentation structure to reach this decision? Second, consider the relevance of the baá¸¥th al-masÄil decision and the ideas of civilizational fiqh produced by the PBNU. To address these two issues, the authors performed a study of the literature based on the primary data from the official document of the baá¸¥th al-masÄil FMPP decision and some results from the PBNU's halaqah fiqh of civilization. The usul fiqh and qawa'id fiqhiya approaches were used in this study, specifically the theory of maslahah and mafsadah in Islamic law. The data in the decision document was then analyzed using content analysis techniques. Based on the data and analysis, it was determined that, first, the Baá¸¥th al-masÄil FMPP decision on the Pancasila issue was formulated based on a solid argumentation with maslaha as its primary paradigm, and the decision's results also demonstrated that Islamic boarding schools have a distinct national fiqh construction. Second, the relevance of the national fiqh construction arising from the baá¸¥th al-masÄil FMPP on Pancasila with the NU civilizational fiqh idea sits in its function as the primary foundation of civilizational fiqh ideas.